Crystallization behavior upon heating and cooling in Cu50Zr50 metallic glass thin films. (December 2016) - Lee, Dongwoo; Zhao, Bingge; Perim, Eric; Zhang, Haitao; Gong, Pan; Gao, Yulai; Liu, Yanhui; Toher, Cormac; Curtarolo, Stefano; Schroers, Jan; Vlassak, Joost J.
Abstract: We have investigated the crystallization kinetics of Cu50 Zr50 metallic glass thin films using nanocalorimetry. The crystallization process is growth-controlled during heating and nucleation-controlled during cooling, resulting in different critical heating and cooling rates to suppress crystallization. Measurements over a wide range of scanning rates (13 K/s to 21, 000 K/s) reveal that crystallization does not follow Arrhenius kinetics upon heating. Instead, the behavior on heating is well described by a fragility-based model of growth-controlled kinetics that takes into account breakdown of the Stokes-Einstein relationship. Upon cooling, the quench rate required to suppress crystallization of the melt is much higher than for bulk samples. This reduced asymmetry in critical heating and cooling rates compared to bulk materials suggests that crystallization of the thin-film metallic glass is controlled by heterogeneous nucleation. Graphical abstract: Image 1